Efektivitas Pendidikan Sebaya Berbasis Digital dalam Mendukung Berhenti Merokok pada Remaja: Tinjauan Sistematis - Kelrey, Dina Setya Rahmah; Permatasari, Henny; Widyatuti, Widyatuti; Rahmadiyah, Dwi Cahya (Universitas Hang Tuah Pekanbaru, 2025)
Smoking behavior among adolescents in Indonesia is increasingly alarming, with the number of active smokers reaching 70 million and a significant rise observed in the 13–15 age group. Early initiation of smoking increases the risk of nicotine addiction, non-communicable diseases, and the economic burden on both families and the nation. This study aims to evaluate the effectiveness of digital peer education in enhancing adolescents’ motivation to quit smoking. Methods: This systematic review was conducted following the PRISMA 2020 guidelines. Article searches were performed in Scopus, ScienceDirect, and ProQuest databases between March and April 2025. Inclusion criteria were developed based on the PICO framework and focused on quantitative studies involving adolescents aged 10–19 years who participated in digital peer education interventions. A total of 10 studies (4 randomized controlled trials, 2 quasi-experimental studies, 2 cohort studies, and 2 cross-sectional studies) met the inclusion criteria and were critically appraised using the JBI Critical Appraisal Checklist. Results: The review revealed that digital peer-based interventions significantly improved adolescents’ self-efficacy, knowledge, and intention to quit smoking. The interventions included online peer education, digital games, social media messaging, and school-based modules. Most studies demonstrated positive outcomes, although variations in evidence strength were noted due to methodological differences, limited follow-up, and reliance on self-reported data. Conclusion: Digital peer education has strong potential as an effective strategy to enhance adolescents’ motivation to quit smoking. Further studies with more rigorous designs and longer follow-up periods are recommended to strengthen the generalizability of these findings.